2022
DOI: 10.1007/s13193-022-01610-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Diagnosis and Surgical Care of Patients with Breast Cancer—a Retrospective Observational Cohort Study from Kerala, South India

Abstract: The COVID-19 pandemic has strained the healthcare system worldwide. Our study aimed to evaluate the impact of the COVID-19 pandemic on the diagnosis and surgical care of patients with breast cancer in Amrita Institute of Medical Sciences, Kochi. This is a single-centre retrospective observational cohort study conducted in a tertiary care institution intended to analyse the management of patients with breast cancer before and after the pandemic outbreak. The number of mammograms dropped from 3689 in the pre-pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A single-center study in India and a multicenter study with five hospitals in the Netherlands reported that the number of BCS decreased during the pandemic. In contrast, the total number of breast surgeries or mastectomies did not change 9,26 . A study using the Kaiser Permanente Northern California Breast Cancer Tracking System database in the United States reported that the percentage of partial mastectomy decreased in 2020 compared with 2019 among patients who underwent surgery as the first treatment 18 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A single-center study in India and a multicenter study with five hospitals in the Netherlands reported that the number of BCS decreased during the pandemic. In contrast, the total number of breast surgeries or mastectomies did not change 9,26 . A study using the Kaiser Permanente Northern California Breast Cancer Tracking System database in the United States reported that the percentage of partial mastectomy decreased in 2020 compared with 2019 among patients who underwent surgery as the first treatment 18 .…”
Section: Discussionmentioning
confidence: 83%
“…Various countries have reported a decrease in the number of breast cancer surgeries during the COVID-19 pandemic 8,9,11,19,[23][24][25][26][27] . Additionally, several studies have examined changes in the number according to the type of surgery; however, the results remain inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation